Eclipsed Justice: The Dissonance between Constitutional Textuality and Legal Reality for Women in Bangladesh - Md. Abdul Mannan Bhuyean (Mimbar Keadilan, 2026)
In Bangladesh, despite the constitutional promise of gender equality, women continue to face significant structural inequalities. The law, while formally recognizing women’s rights, often fails to materialize in practice, creating a gap between legal norms and social realities. This article seeks to explore the disjunction between the legal texts that guarantee gender equality and the persistent discrimination experienced by women, focusing on unequal access to social and economic justice as well as legal protections that do not lead to genuine empowerment. This study employs a doctrinal legal research method with a critical theoretical approach, specifically feminist legal theory and critical justice theory. The author critiques the Bangladeshi legal system, which continues to operate within a masculine and patriarchal framework, both in its constitutional domain and criminal law. The main findings reveal that although statutes such as the Prevention of Women and Children Repression Act (2000) and the Anti-Dowry Act (1980) provide legal safeguards, women remain marginalized by procedural and structural inequities. The existing legal system is not sufficiently transformative to ensure substantive justice for women. Hence, a more inclusive and transformative legal approach is required to realize genuine equality.